Financial Performance Analysis of Village Unit Cooperatives (Koperasi Unit Desa) Karangploso, Malang Regency - Maria Dominika Agni; Anung Prasetyo Nugroho; Moch Nurhidayat (International Research & Development for Human Beings (IRDH), 2026)
This study aimed to determine the financial performance of KUD Karangploso for the last five years by analyzing the parameters of liquidity, solvency, and profitability. This study uses a quantitative descriptive research design. The data was used as financial statements for the KUD Karangploso period 2019-2023. Data analysis using ratio analysis in the form of liquidity analysis (Current Ratio and Cash Ratio), solvency ratio (Net Worth to Debt Ratio and Debt to Equity Ratio), activity ratio (Fixed Asset Turnover Ratio and Debt to Equity Ratio), and profitability ratio (Return on Assets and Return on Equity). The analysis results show that the financial performance of KUD Karangploso, based on the solvency ratio, faces challenges in maintaining its liquidity because the ratio value is below the standard.Furthermore, the analysis of solvency ratios shows good performance, although fluctuating, and analysis of Net Worth to Debt Ratio in 2019. Moreover, the study of profitability ratios shows unhealthy financial performance (ineffective). Karangploso Village Unit Cooperative (KUD) managers need to improve the efficiency of cash management and current assets, balance the capital structure by reducing long-term debt and increasing equity, and improve the effectiveness of asset management and equity to generate optimal profits through business diversification, increased operational efficiency, and product and service innovation.